Developing Islamic Nuanced Learning Module of Rectangular for Junior High School Students - Junarni, Junarni; Hidayah, Nurul; Rakhmawati, Rosida; Putra, Rizki Wahyu Yunian (Universitas Negeri Surabaya, 2020)
This study aims to develop Islamic nuanced module of rectangular for junior high school students and to determine students' responses to teaching materials in the form of Islamic nuanced learning module of rectangular. This study uses research and development (R&D) methods with the ADDIE development model. There are five stages in this model, namely Analyze, Design, Development, Implementation, and Evaluation. The learning module were validated by several experts namely material experts, media experts, and religious experts. The results of the study showed that the Islamic mathematical modules on the rectangular material developed met valid and practical criteria. The validity of the module, assessed by material experts, media experts, and religious experts show respectively the percentage of 87%, 88%, and 91% which are included in the